Cost and profitability of tomato cultivation in a protected environment with different spacings - Festl, Max José; da Silva Ponce , Franciely; Theis de Aguirre, Josiane Marlise; de Oliveira Velozo, Paulo Henrique; Roggia Zanuzo, Márcio; Rodrigues Abadio de Paula , Ana Karina; Graciele Hülse de Souza, Silvia; Seabra Júnior, Seabra Júnior (Comunicata Scientiae, 2025)
The tomato (Solanum lycopersicum L.) is a crop of great global economic importance due to its extensive cultivation area, in addition to generating employment and income. Climatic conditions are a major obstacle to production, requiring the use of a protected environment to produce quality fruits. Thus, the objective of this study was to analyze the cost and profitability of tomato cultivation in a traditional cultivation environment, covered with plastic film, and in a cultivation environment covered with polycarbonate and water film, using different spacings as a decision-making criterion. The experiment was conducted in the experimental area of Embrapa Agrossilvipastoril in the municipality of Sinop - MT. Different environments were used: greenhouse covered with 150 micron agricultural film and greenhouse covered with polycarbonate with the application of a water film for cooling and five spacings: 0.2; 0.3; 0.4; 0.5 and 0.6 m. Commercial productivity, total operating cost and profitability were evaluated. For both environments, the 0.2 and 0.3 m spacings showed greater productivity and consequently gross revenue, which was reflected in profitability parameters such as operating profit, gross margin, profitability index, leveling point and price. The other spacings tested did not show economic viability.